The impact of the Supervisor's Role in training Programmes on the transfer of training : A case study in four East Malaysian Local Governments - Ng , Kueh Hua; Ahmad, Rusli; Ismail, Azman (Curtin University of Technology, 2011)
The Malaysian public sector plays a key role in the government's vision to enhance the economic status, assist the growth of industrial and private sectors, and support the country's human capital needs. Extant studies advocated that a supervisor plays an important role in enhancing the transfer of training among employees, and although the nature of this relationship has been studied, it is has been given less attention especially in the context ofthe Malaysian public sector. Hence, this study attempted to rectify the lack of literature by investigating the relationship between a supervisor's role in training programmes, and the transfer of training in four East Malaysian local governments. Indepth interviews were conducted with a total of 12 employees to develop the self report questionnaire, and a pilot study was conducted with the participation of 60 employees to pre test the questionnaire. The questionnaire was then used to gather quantitative data from 1100 management and non management employees working in the administrative and technical divisions for hypotheses testing. Pearson correlation analysis showed a positive and significant relationship between supervisor's role in training programmes and the transfer of training. Multiple regression analysis demonstrated among the studied variables, supervisor communication acted as a dominant factor in enhancing the transfer of training. These findings have implications for human resource management (HRM) policies and practices by detailing guidelines to improve organisational remuneration system as well as pathways for enhancing the role of supervisors in training programmes in order to facilitate the transfer of training, particularly within the Malaysian public sector.